2020
DOI: 10.15388/ekon.2020.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Energy Consumption on GDP: New Evidence of 24 Countries on Their Natural Resources and Production of Electricity

Abstract: Because of rapid economic expansion, China, the USA, and India have become the largest energy producers and sources of CO2 emissions in the world. They burned over 45% of global fuels in 2016. Meanwhile, the developing strategies of 24 polluted states to decrease fossil energy consumption without additional economic output. This paper explores the effect of world top polluted countries’ CO2 emission, their GDP and production of electricity by potential indicators and identifies the basic factors that contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Because of high pressure, China cut its CO2 emissions from all sources of coal and announced it would cut CO2 emissions (per-unit) of GDP by 40% to 45% in 2020 from 2005 [ 40 , 72 , 73 ]. While as for the reduction of CO2 emissions, environmental quality and water shift from coal to shale gas will improve consumption and public health [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because of high pressure, China cut its CO2 emissions from all sources of coal and announced it would cut CO2 emissions (per-unit) of GDP by 40% to 45% in 2020 from 2005 [ 40 , 72 , 73 ]. While as for the reduction of CO2 emissions, environmental quality and water shift from coal to shale gas will improve consumption and public health [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Paul & Bhattacharya (2004) and Bunnag (2023) have found a two-way causal relationship between energy consumption and economic growth in Thailand and India, respectively. Other studies by Khan and Kong (2020) and Jayasinghe et al (2022) have found a unidirectional causal relationship between energy consumption and GDP in the short and long-run. However, studies by Ahmad et al (2020aAhmad et al ( , 2020b have found a bidirectional causal relationship between investment in energy and regional product growth in China.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Most studies are analyses of statistical inferences of countries or a country studied in isolation. There are many studies covering various economies [28][29][30][31][32][33][34], for example [35][36][37][38]. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…[36], 53 countries for Ref. [37], and in [38], 24 countries are heterogeneous economies. However, when observing the studies that opt for groups, there is a direction to investigate specific groups with some similarities, whether geographical, economic and cultural, among others.…”
Section: Discussionmentioning
confidence: 99%